The Application of The Google Form Media to Increase Student Learning Motivation at Kandangan 4 Elementary School - Ninik Sulis Setiani; Esti Untari; Sri Kustiyah (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2022)
This study aims to determine the use of google form media to increase the learning motivation of grade 4 students at Kandangan 4 Elementary School, Kandangan District. The research was conducted with a qualitative approach to the type of classroom action research. The research was carried out in two cycles, each consisting of 4 stages, namely planning, implementation, observation, and reflection. The data obtained are process data and result data. Collecting data using interview techniques, observation, tests, documentation, and field notes. Data analysis was carried out with the stages of reducing data, presenting data, and drawing conclusions. The results showed that the application of google form media can increase students' learning motivation. This is evidenced by the increase in teacher activity from 81.25% in the first cycle to 93.5% in the second cycle. The student activity increased from 81.8% in the first cycle to 90.9% in the second cycle. Meanwhile, the level of student motivation also increased from 66.5% in the pre-action to 84.8% in the first cycle and 88% in the second cycle. Teachers are expected to continue to develop online learning through the right and correct google form, and add some references about online learning that are more innovative and interesting for students in achieving the expected goals.